2020
DOI: 10.1097/md.0000000000021992
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of Conbercept in the treatment of diabetic macular edema based on OCTA

Abstract: Background: Diabetic macular edema (DME) can cause severe vision impairments for patients with diabetes. Recently, Conbercept has shown efficacy on DME with 3-monthly loading dose injection and pro re nata (PRN, 3+PRN) thereafter in retrospectivetrials. Furthermore, there are some other approaches have been recommended such as 2mg bimonthly (2q8) after 5 initial doses, or Conbercept 0.5mg treat-and-extend, however, some patients still have recurrence of the disease after treatment. Therefore, in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“… 9 , 10 No capillary perfusion, tissue inflammation, ischemia and hypoxia can increase vascular permeability and further aggravate macular edema, and long-term diffuse macular edema can cause severe visual damage. 11 , 12 Moreover, the treatment method of CRVO combined with macular edema is limited, and the efficacy is poor, which seriously affects the physical and mental health of patients. 13 Therefore, it is urgent to explore relevant biological evaluation indexes for early detection and timely treatment in clinic, so as to improve the prognosis of patients with CRVO combined with macular edema.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 No capillary perfusion, tissue inflammation, ischemia and hypoxia can increase vascular permeability and further aggravate macular edema, and long-term diffuse macular edema can cause severe visual damage. 11 , 12 Moreover, the treatment method of CRVO combined with macular edema is limited, and the efficacy is poor, which seriously affects the physical and mental health of patients. 13 Therefore, it is urgent to explore relevant biological evaluation indexes for early detection and timely treatment in clinic, so as to improve the prognosis of patients with CRVO combined with macular edema.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from retrospective studies have shown that 3-monthly loading-dose intravitreal injections of Conbercept as well as pro re nata (PRN) treatment were efficacious in treating DME [50,69,70]. An ongoing multicenter, randomized, single-masked clinical trial will be the first to evaluate the safety and the therapeutic effect of 6 + PRN vs. 3 + PRN regimen in patients with DMO [71]. This could allow for a development of a better treatment strategy.…”
Section: Ocular Treatment Of Diabetic Retinal Diseasesmentioning
confidence: 99%
“…It has been widely utilized in clinical settings (5)(6)(7). Research has substantiated the effectiveness of conbercept in managing DME (8,9) and PDR (10,11). Initial reports of DRSS score improvements postanti-VEGF injections emerged from clinical trials focusing on DME.…”
Section: Introductionmentioning
confidence: 99%